Asuhan Keperawatan Medikal Bedah dengan Intervensi Penerapan Slow Stroke Back Massage Therapy pada Pasien Stroke Non Hemoragik dengan Masalah Perfusi Serebral Tidak Efektif dan Gangguan Mobilittas Fisik di Ruang Flamboyan RSUD dr. T.C Hillers Maumere - Kristina Tala Da Silva; Agustina Dua Wida (Pusat riset dan Inovasi Nasional, 2024)
Non-hemorrhagic stroke is a clinical sign of dysfunction or damage to brain tissue caused by lack of blood flow to the brain, thereby disrupting the need for blood and oxygen in brain tissue. Slow stroke back massage therapy is a non-pharmacological therapy to overcome problems in patients with stroke. This research aims to be able to carry out nursing care for clients with non-hemorrhagic stroke using slow stroke back massage therapy in the Flamboyan Room at RSUD dr. T.C Hillers Maumere. The research design used was a case study. The approach used is a nursing care approach which includes identifying data from assessment results, nursing diagnoses, planning, implementation and evaluation. Slow stroke back massage therapy is carried out for 3 days. Data collection techniques used a medical-surgical nursing care assessment format, observation and literature study. The results of the case study showed that clients were diagnosed with ineffective cerebral perfusion and impaired physical mobility. The application of slow stroke back massage therapy showed improvements or changes on the third day, which resulted in the client experiencing a decrease in blood pressure from 180/100 mmHg to 160/90mmHg, not complaining of dizziness, and the patient's right hand was starting to be able to move. The conclusion of this case study is that slow stroke back massage therapy is effective in reducing blood pressure and also helps in increasing physical mobility in non-hemorrhagic stroke patients.